ENHANCING DIGITAL PEDAGOGICAL COMPETENCE OF RELIGIOUS SUBJECT TEACHERS AT MADRASAH ALIYAH NEGERI 3 PALEMBANG - Dadang, Dadang; Idi, Abdullah; Abdurrahmansyah, Abdurrahmansyah; Fauzi, Muhamad (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Background: This research is premised on the growing necessity for religious education teachers to possess digital pedagogical competencies, particularly in light of the current educational landscape. Digital pedagogical competency refers to a teacher's ability to effectively integrate digital technologies into the teaching and learning process. Given the rapid advancement of digital tools and their increasing relevance in education, this competency has become critical for fostering innovation in teaching methods. Purpose: The primary aim of this study is to analyze the various efforts made to enhance the digital pedagogical competence of religious subject teachers at Madrasah Aliyah Negeri 3 (MAN 3) in Palembang City. By examining these efforts, the research seeks to understand how teachers are improving their ability to integrate technology into their instructional practices. Method: Using a qualitative case study approach, data were collected through observations, interviews, and document analysis. Result: The findings reveal several strategies employed to improve these competencies: participation in ICT-focused training and workshops, peer learning through collaboration with colleagues adept in technology, self-directed learning via online resources like YouTube, and active involvement in professional forums such as Subject Teachers' Conferences (MGMP) and Madrasah Working Groups (KKM). Conclusion: The study highlights the diverse and proactive approaches taken by teachers to improve their digital pedagogical competencies, underscoring the importance of continuous professional development and collaborative learning in enhancing the integration of digital technologies in religious education.